Mesopotamia return to Eden - Gardner, Robert; Westbrook, Joel (Time-Life's lost civilizations, 1995)
Unearth physical clues to the truth behind the biblical stories of Noah and his ark, the Great flood, the Tower of Babel, etc. Embark on thought provoking "Return of Eden" to the barbaric reign of the Assyrians to the drawn of civilization amid the first cities of ancient Sumer. Witness the invention of writing, the wheel and the concept of law.